1991
DOI: 10.1093/carcin/12.6.1115
|View full text |Cite
|
Sign up to set email alerts
|

Unusually high levels of carcinogenic tobacco-specific nitrosamines in Sudan snuff (toombak)

Abstract: The aim of these studies was to determine the levels of carcinogenic tobacco specific nitrosamines (TSNA) in Sudanese oral snuff (toombak) as recent retrospective epidemiological studies suggested an association between the use of toombak and subsequent development of oral cancer. We have analyzed the TSNA levels in 20 samples of Sudanese toombak, of four different quality levels, collected from five different vendors. Using GC coupled with thermal energy analysis, four TSNA were quantified in snuff extracts: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(55 citation statements)
references
References 0 publications
3
52
0
Order By: Relevance
“…and N H -nitrosoanabasine (NAB) were quanti®ed in toombak and saliva of toombak users [15,16]. Exceptionally high levels (mean; range, mg/g toombak/dry wt) of NNN (1.13; 0.50±3.08), NNK (2.31; 0.62±7.87; 31), NAT (0.08; 0.02±0.2) and NAB (0.22; 0.02±2.37) were found (Table 1).…”
Section: N-nitrosaminesmentioning
confidence: 99%
See 1 more Smart Citation
“…and N H -nitrosoanabasine (NAB) were quanti®ed in toombak and saliva of toombak users [15,16]. Exceptionally high levels (mean; range, mg/g toombak/dry wt) of NNN (1.13; 0.50±3.08), NNK (2.31; 0.62±7.87; 31), NAT (0.08; 0.02±0.2) and NAB (0.22; 0.02±2.37) were found (Table 1).…”
Section: N-nitrosaminesmentioning
confidence: 99%
“…Much later, it was found that 81% (50/62) of patients with oral squamous cell carcinoma (SCC) from the Sudan used toombak [36]. Recently, abundant information on toombak use and development of oral cancer has been reported, and the cancer was frequently found at the site where the toombak quid is placed [9,12,15,16,21]. Studies of a similar nature from Saudi Arabia have suggested the aetiological role of Shamma for development of oral cancer [37,38].…”
Section: Oral Cancermentioning
confidence: 99%
“…The American, Sudanese and Yemeni products had comparable bacterial loads. However, studies indicate that they significantly vary with respect to their TSNA content [39]; SuT in particular has very high concentrations of TSNAs [40]. Obviously then, the levels of TSNAs in ST products differ not only as function of total microbial load but probably also as a function of microbial community composition.…”
Section: Discussionmentioning
confidence: 99%
“…A standard curve was generated by running 10-fold serial dilutions of E. coli DH10B genomic DNA. Amplification was carried on a ViiA7 platform (Applied Biosystems, USA) including an initial enzyme activation cycle at 95°C for of 10 min followed by 40 (AGAGTTTGATYMTGGCTCAG) [24] and 519R (GWATTACCGCGGCKGCTG) [25], modified to contain Illumina's specific adapter sequences 803F and 1392wR, were used to amplify the V1-3 region of the 16S rRNA gene using standard PCR conditions. The resultant PCR amplicons (~ 520 bp) were then purified (Agencourt AMPure XP beads, Beckman Coulter, USA), indexed with unique 8-base barcodes (Nextera XT v2 Index Kit sets A-D, Illumina, USA) and pooled together in equimolar concentrations.…”
Section: Determination Of Bacterial Loadmentioning
confidence: 99%
“…The nitrose amines levels that found in Tobacco are high in toombak [10], attributed to the type of tobacco Species and way of processing toombak at high temperature, prolonged storage, and contamination during processing [11][12][13].…”
Section: Discussionmentioning
confidence: 99%